Surrogate Motherhood in Greece: Statistical Data Derived from Court Decisions - Ραβδάς (Pantelis Ravdas), Παντελής (Bioethica, 2017)
Gestational surrogacy is legal in Greece since 2002, under conditions that include a court decision granting permission prior to the transfer of reproductive material to the gestational surrogate. Quantitative and qualitative statistical data compiled from 256 relevant court decisions issued between 2003 - 2017 outline the profile of intended mothers (and fathers) that resorted to gestational surrogacy as well as the profile of women that offered to become gestational carriers. Core aspects of the evergreen legal and social debate on surrogate motherhood are revisited under the light of this indicative part of its application in practice.